Resonasi Leksikal dalam Terjemahan al-Qur’an Berbahasa Inggris: Analisis Alih Bahasa Surah aṭ-Ṭāriq Shawkat M. Toorawa - Wafiudin, M. Afif; Yardho, Moh.; Hakim, Muhammad Naufal (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This study examines the translation method proposed by Shawkat M. Toorawa, with an emphasis on efforts to preserve lexical resonance. The focus of this research is on Toorawa’s approach in translating Surah aṭ-Ṭāriq into English. This research employs a qualitative descriptive-analytical model and is a form of library research. The findings reveal that Toorawa’s translation process involves three steps: 1) Cataloging hapax; 2) Pay attention to lexical echoes; 3) Translate it in English. Specifically, Toorawa’s approach to translating Surah aṭ-Ṭāriq involves rendering and interpolating meanings to achieve a translation that resonates in both tone and meaning.